Eco-Friendly Opportunities and Strategies of The Black Soldier Fly Maggot Business in Pariaman, West Sumatera - M Ikhwan; Rachmat Pambudy; Etriya Etriya (Jurnal Manajemen dan Agribisnis, 2025)
Background: Food Loss and Food Waste (FLW) may have a significant impact on the global economy, environment, and food security. However, this problem also presents a business opportunity through the production and processing of Black Soldier Fly (BSF) maggots that utilize organic waste. Purpose: This paper aims to create a business model with Bank Sampah Sahabat Alam (BSSA) serving as the primary unit of analysis, formulate strategies, and prioritize strategies of the BSF maggot business in Pariaman, West Sumatera, to seize opportunities and use local resources. Design/methodology/approach: The data were analyzed using Business Model Canvas (BMC), Internal-External (IE), and SWOT matrices to formulate strategies, and Quantitative Strategic Planning Matrix (QSPM) to prioritize strategies. Findings/Result: The results demonstrate that the BSF maggot business is in a growth position, with intensive and integrative strategies recommended. The QSPM suggests prioritizing the political support of the Mayor of Pariaman for the development of this business, support from local governments plays a crucial role in determining business success by influencing policy formulation and resource allocation, which is critical to ensuring effective business planning and driving sustainable growth. Modified the BMC of the BSF maggot business in Pariaman with improvements in all BMC segments to support more effective strategy execution.Conclusion: Strategy formulation through the SWOT Matrix resulted in 10 alternative strategies classified into intensive and integrative strategies from the IE matrix results. Strategy priorities for the BSF maggot business in Pariaman have been determined through QSPM analysis. The implementation of these strategies brings an update to the BMC, which provides a comprehensive guide for business development and optimization in a sustainable and eco-friendly manner. Originality/value (State of the art): This paper makes a new contribution in the application of strategies generated from a combination of internal and external environmental analysis, including VRIO, Porter's Five Forces, PESTEL, as well as Internal-External (IE) and SWOT matrices, into Business Model Canvas (BMC) elements for the BSF maggot business. This holistic approach provides a more comprehensive strategic guide to deal with the sustainable business dynamics in this sector. Keywords: BSF maggot business, business strategies, business model canvas, food waste, opportunities